2021
DOI: 10.1186/s40795-021-00437-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of undernutrition and its associated factors among pregnant women in Konso district, southern Ethiopia: a community-based cross-sectional study

Abstract: Background Undernutrition during pregnancy is an important public health problem. It is highly prevalent in Ethiopia but not sufficiently addressed yet. Hence, this study aimed to assess the prevalence of undernutrition and its associated factors among pregnant mothers in Konso district, Ethiopia. Methods Community-based cross-sectional study was conducted with a qualitative inquiry from December 2018 to January 2019. A multistage stratified sampli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 38 publications
2
16
1
Order By: Relevance
“… 63 In line with this, the occurrence of undernutrition in this research was found four times greater than the cutoff value to declare maternal undernutrition as a main public health issue, which is 10%. 8 , 63 , 64 The prevalence was also consistent with previous studies, 40 , 42 , 65 , 66 and higher than other study findings 37 , 38 conducted in different parts of Ethiopia. The reasons for the higher prevalence in eastern Ethiopia might be due to variations in socio-demographic characteristics, study setting, sample size, and population.…”
Section: Discussionsupporting
confidence: 89%
“… 63 In line with this, the occurrence of undernutrition in this research was found four times greater than the cutoff value to declare maternal undernutrition as a main public health issue, which is 10%. 8 , 63 , 64 The prevalence was also consistent with previous studies, 40 , 42 , 65 , 66 and higher than other study findings 37 , 38 conducted in different parts of Ethiopia. The reasons for the higher prevalence in eastern Ethiopia might be due to variations in socio-demographic characteristics, study setting, sample size, and population.…”
Section: Discussionsupporting
confidence: 89%
“…This study aimed to assess the maternal undernutrition and associated factors among pregnant women at the public hospitals of Bench-Sheko and Kaffa zone, Southwest Ethiopia. According to this study, the prevalence of maternal undernutrition among pregnant women was 42.4%, which is almost consistent finding with the study from the Guji zone (41.2%) [ 21 ], Tigray region, (40.6%) [ 23 ], from the rural district of Oromia region (41%) [ 3 ], Konso district of Ethiopia (43.1%) [ 26 ] and India (38%) [ 27 ]. This alignment might be because the measurement cut-off points used were similar to this study's cut-off points for undernutrition, which all used <23 cm, and the socio-economic status of the study participants.…”
Section: Discussionsupporting
confidence: 89%
“…Different interventions have been undertaken to curb the high prevalence of maternal undernutrition in the past years by the Ethiopian Federal Ministry of Health and other stakeholders ( 28 , 29 ). However, high maternal undernutrition is still a challenge in many parts of the country ( 15 , 23 ). We found that 14 percent of women were undernourished which is less than what was reported in the previous studies ( 24 , 26 , 30 ).…”
Section: Discussionmentioning
confidence: 99%